Retention in the Bukhali trial in Soweto, South Africa: a qualitative analysis using self-determination theory - Shane A Norris; Stephen Lye; Catherine E Draper; Nosibusiso Tshetu; Nokuthula Nkosi (BMJ Global Health)
Introduction There is limited research on applying theory to retention in complex intervention trials. To address this gap, this study aimed to qualitatively examine retention in the Bukhali randomised controlled trial, from the perspective of trial participants and staff, through the lens of self-determination theory (SDT). The Bukhali trial is part of the Healthy Life Trajectories Initiative in Soweto, South Africa, with young women.Methods Nine focus group discussions were used to generate data from Bukhali trial staff (n=45, 23–64 years), and participants, including those currently enrolled (n=16, 25–31 years) and those who had withdrawn from the trial (n=20, 24–32 years). A codebook thematic approach was taken to data analysis; SDT was used to develop a conceptual model to analyse the data in context. The main themes identified were external influences on the trial, trial implementing environment, controlled motivation and intrinsic autonomous motivation.Results Our findings highlighted the contextual issues influencing the trial, including participants’ socioeconomic circumstances, and the presence or absence of social support, the trial complexity and participant burden. Issues related to controlled motivation comprised challenges of staying in contact, financial incentives and food, health services provided and other incentives. We also identified aspects of the trial supporting participants’ psychological needs of autonomy, competence and relatedness, which in turn contributed to their intrinsic autonomous motivation. These included participants’ interest in the trial and its relevance to them; participants’ sense of agency, meaning and purpose through their involvement; the building of their knowledge and awareness about their health; relating to other participants and the relationships built with staff and being treated well.Conclusion SDT provides a helpful frame for a contextualised understanding of the complexity of retention of Bukhali trial participants (longitudinal study and intervention). These findings have relevance for trials in under-resourced settings.